Intelligent traffic signal control system based on fuzzy approach technique for multilane-multiple intersection - Azura Che Soh, 1975-; Marzuki Khalid, supervisor; Rubiyah Yusof; Mohammad Hamiruce Marhaban; Fakulti Kejuruteraan Elektrik (2011)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2011